A study on factor that influence ownership of residential property in Melaka / Ummu Umairah Mohd Yunus - Mohd Yunus, Ummu Umairah (2009)
Despite its flexibility, the residential property sector is getting increasingly competitive and the developers are looking at the slower take-up rates and flattish earnings performance. Property developers have to confront challenges in maintaining market share and profit margin. The developers have to keep themselves updated with the current market situation and hence, to develop the strategy that can enable them to boost the sales of the houses. This study has four objectives to be achieved. This is to study which factor such as first ; location, second ; types of property and third ; disposable income that contribute most to the ownership of the residential property in Melaka, and the fourth objective is to study the relationship between real cost afford and income by people of Melaka to be the owner of a residential property. Therefore, this study has been developed with the aim to identify the most influential factor that contributes to the ownership of residential property in Melaka. The study was conducted through questionnaires with selected residents at the chosen housing area around Melaka. The data were analyzed using SPSS Software. It was found that the most influential factor is disposable income of the respondents. Furthermore, location is also a very important factor that contributes to the ownership of residential property in Melaka.